PENGARUH PERHATIAN ORANG TUA TERHADAP PEMBELAJARAN AKIDAH AKHLAK DIMASA COVID-19 PADA SISWA KELAS VIII MTS YASPEND MUSLIM PEMATANG TENGAH - Khairul Bariah; Kamaliah, Syarifah (STAI Jama'iyah Mahmudiyah Tanjung Pura, 2022)
This study aims to determine the relationship between parental attention and morals learning. Then the researchers conducted a theory test by collecting theories related to the research variables discussed. The method of collecting data is by means of interviews, tests and questionnaires. Data management techniques are obtained from questionnaires that have been answered by students and tabulated on a frequency table to find the percentage of each student's answers. After that the results of student answers are entered in the score table and added together so that the number of each student's answer score is obtained. The results of this study indicate that there is a positive and significant relationship between parents' attention to the learning of moral aqidah. The calculation result obtained from the correlation is 0.623. After calculating the product moment, the researcher compares it with the correlation table at a significant level of 5% and a significant level of 1%. . This shows that the calculation result is greater than the correlation table at both the 5% and 1% levels. This shows that there is a positive and significant relationship between parents' attention to the learning of aqidah morality. Furthermore, the researcher looks at the table that determines the level of relationship between each variable. These results indicate that the level of correlation is moderate or sufficient.